Long Non-Coding RNA Expression Profiling in Aging Rats with Erectile Dysfunction - Lianjun Pan; Jiehua Ma; Feng Pan; Dan Zhao; Jianping Gao (Cellular Physiology and Biochemistry, 2015)
Background/Aims: Erectile dysfunction (ED) in aged people remains a topic of interest to andrological physicians. Long non-coding RNAs (lncRNAs), which form the largest group of non-coding RNAs, have been shown to regulate various biological processes. The function of lncRNAs in age-related erectile dysfunction (A-ED) pathogenesis remains poorly understood. Methods: This study aims to assess the differential expression profiles of mRNAs and lncRNAs between A-ED and normal control (NC) samples. Using a second-generation lncRNA microarray, we detected a total of 8,744 lncRNAs and 13,585 coding transcripts. Results: We identified 608 up-regulated and 406 down-regulated lncRNAs in A-ED compared with NC samples, by setting a filter of fold-change >2.0. Gene Ontology and pathway analysis revealed that a muscle contraction disorder induced by abnormal ion channels might play a critical role in the pathogenesis of A-ED. Conclusion: Our results show significantly altered expression profiles of lncRNAs and mRNAs between A-ED and NC. This study may provide information for further research on A-ED and may be helpful for finding a new therapeutic target for A-ED.